Triethyl phosphate (TEP) – dimethylsulfoxide (DMSO), as a green solvent mixture for solid-phase peptide synthesis (SPPS) - Sikabwe Noki; Luana Lastella; Simona Serban; Alessandra Basso; Gyorgy Orosz; Beatriz G de la Torre; Fernando Albericio (Green Chemistry Letters and Reviews)
The free use of DMF has recently been restricted since December 2023 in Europe because of its health hazards. Over time, these restrictions will extend to the USA and other countries. As DMF is the solvent of choice for solid-phase peptide synthesis (SPPS), its replacement has become an important issue. So far, there is not a solvent alone that shows possible replacement of DMF, consequently, several mixtures have been proposed. Herein, the triethyl phosphate (TEP) is proposed as an excellent alternative to EtOAc/BuOAc for use in combination with DMSO for SPPS at rt. TEP has shown broad application as a flame retardant in the plastics manufacturing industry due to its negligible level of toxicity, non-carcinogenicity, non-mutagenicity, and non-bioaccumulative properties. The performance of TEP-DMSO (3:1) in SPPS has been demonstrated by the synthesis of three medium-sized peptides of interest (Angiotensin, Afamelanotide, and the C-terminal peptide of Tirzepatide) with excellent purity at rt. Furthermore, TEP-DMSO (3:1) results in slightly less racemization than DMF in peptides containing Cys/His. Finally, it has been demonstrated that Ramage resin is more secure to use than Rink-amide resin because it does not break out during the final global deprotection step, avoiding the formation of linker-related side-products.